The Management of a Bottling Service: Modelling Schedules to Optimise Capacity - Tsapo, Otsile \olebogeng (2013)
Purpose The purpose of this research is to explore the feasibility of building a bottling plant in the East Midlands region to serve micro-breweries in this region. A capacity planning and scheduling analysis shall be undertaken to help realise the goal. Recommendations from the analysis will be made on how best to schedule capacity of the plant. Design/Methodology/Approach To achieve the goal, a scheduling model shall be built to help optimise capacity. The model shall use quantitative data obtained from observations, a survey and meetings with the stakeholder. Qualitative data will be used to beef up the recommendations with data from the industry. Findings A linear programming model was created using some techniques from the Vehicle Routing Problem. The model was solved on Excel Solver to find the schedule that best optimises capacity. Value A model was created using techniques from Vehicle Routing Problem and linear programming. To my knowledge, this has not been done before. All formulas are retained in the model making it user friendly. Keywords Capacity planning, capacity strategies, scheduling, Vehicle Routing Problem, Linear programming.